2014
DOI: 10.1177/0014402914532232
|View full text |Cite
|
Sign up to set email alerts
|

Parents’ Views of Schools’ Involvement Efforts

Abstract: Individual and focus group interviews were conducted with 96 parents of students with disabilities in 18 schools to explore parents’ views of schools’ efforts to engage them in their child’s education. A mixed-methods approach was used to identify and evaluate the relative importance of eight themes related to schools’ efforts to facilitate parent involvement and parents’ involvement with their child at school. The results suggest important relationships among parents’ initiative to become involved, their perc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
0
2

Year Published

2016
2016
2025
2025

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(29 citation statements)
references
References 36 publications
1
26
0
2
Order By: Relevance
“…There are some supporting ideas about the parents-involvement in the school deals the students with disabilities. (Rodriguez, Blatz, & Elbaum, 2014)explain that the school staff, including teachers, not only communicated with the parents about students' progress but also frequently mentioned that the teachers were accessible. There was a room to communicate, it is called Individualized Education Program (IEP) meeting, the result explain that the parents' involvements bring the child's progress and allow the parents a variety of communication methods.…”
Section: Parents' Involvementmentioning
confidence: 99%
“…There are some supporting ideas about the parents-involvement in the school deals the students with disabilities. (Rodriguez, Blatz, & Elbaum, 2014)explain that the school staff, including teachers, not only communicated with the parents about students' progress but also frequently mentioned that the teachers were accessible. There was a room to communicate, it is called Individualized Education Program (IEP) meeting, the result explain that the parents' involvements bring the child's progress and allow the parents a variety of communication methods.…”
Section: Parents' Involvementmentioning
confidence: 99%
“…Initially, this means that teachers should show CLD families that they are interested in getting to know and working with them, such as proactively welcoming CLD families to the IEP team, initiating conversations with them, and inviting their participation. Eventually, and within the relationshipbuilding process, teachers should engage in purposeful and individualized efforts to encourage meaningful engagement in IEP meetings by CLD families (Rodriguez, Blatz, & Elbaum, 2014a).…”
Section: Guiding Question 2: Who Is This Family?mentioning
confidence: 99%
“…(F12) Several studies have reported significant levels of parental dissatisfaction with the special educational system. Lack of specialist professional knowledge in schools has been identified as frustrating for parents of children with autism (Iadarola et al, 2015) as has schools' willingness to listen to or take account of parental perspectives (Rodriguez, Blatz, & Elbaum, 2014). At a systems level, parents have criticised processes leading to statements of special educational needs in the UK (Lamb, 2009) and tribunals concerning placement decisions (Penfold, Cleghorn, Tennant, Palmer, & Read, 2009).…”
Section: Attitudinal Issuesmentioning
confidence: 99%
“…At a systems level, parents have criticised processes leading to statements of special educational needs in the UK (Lamb, 2009) and tribunals concerning placement decisions (Penfold, Cleghorn, Tennant, Palmer, & Read, 2009). However, it is difficult to compare levels of maternal and paternal satisfaction due to a lack of information concerning the sex of participants (as in The Lamb Enquiry) or because analysis has not been disaggregated by gender, (see Rodriguez, Blatz, & Elbaum, 2014).…”
Section: Attitudinal Issuesmentioning
confidence: 99%